Characterization of the foundation soil for the expansion of the scientific base 'Machu Picchu' Antarctica - Hernández Aguilar, Marco Antonio (2023)
This report presents a geotechnical analysis of the soils in the area of ​​the Machu Picchu Peruvian scientific base, located at Punta Crepin, on the Antarctic peninsula. The work carried out is part of the soil studies necessary to define the foundation conditions for the future expansion and installation of new research modules at the base. During the ANTAR XXVI expedition in 2019, the final geotechnical campaign was carried out to carry out a detailed reconnaissance of the soils that will serve as support for the foundations to be defined at the Peruvian base. This campaign included field work, carrying out 12 pits, 24 density tests and obtaining samples from the strata. These normal and special field and laboratory tests, in representative samples, will allow characterizing the soils under study. The results obtained reveal that in Punta Crepin there is a superficial layer composed of polymictic gravels with intercalations of medium massive sandstones, typical characteristics of marine terraces. These soils cover most of the extension of the base. In addition, a predominantly gravel structure has been identified in the underlying strata, resulting from the erosion of morainic deposits and the formation of an alluvial-fluvial system. This formation with good load capacity will be used for the foundation of the new scientific modules at the base. Considering the severe weather conditions and the existing soils, a special foundation is proposed to guarantee the stability of the structures to be built.